Correction of the type species of the South American genus Gromphas Brullé, 1837 (Coleoptera: Scarabaeidae: Scarabaeinae: Phanaeini) - Cupello, Mario; Vaz-De-Mello, Fernando Z. (Zootaxa, 2014)
Recently, we (Cupello & Vaz-de-Mello, 2013) presented a taxonomic revision of the dung beetle genus Gromphas Brullé, 1837 in which we recognized the validity of five species: Gromphas aeruginosa (Perty, 1830), G. amazonica Bates, 1870, G. dichroa Blanchard, 1846, G. inermis Harold, 1869, and G. lemoinei Waterhouse, 1891. In that work, we also confirmed that Gromphas was described by Brullé (1837) without any included species and that the widely cited name “Gromphas lacordairei Brullé” was never formally described or cited by Brullé and, in fact, all citations to this name refer to G. lacordairii Burmeister, 1874, a junior synonym of G. inermis Harold, 1869. Thus, the question of the identity of the type species of Gromphas remained open.